HISTORY, IDEOLOGICAL ASPECTS AND FUTURE VISION OF AAM AADMI PARTY - Jaiswal, Rakesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Aam Aadmi Party, as an Indian political party, was formally established on 26 November 2012. Anna Hazare, the prominent fasting leader of the anti-corruption movement, and his activist Arvind Kejriwal had a disagreement on the issue of whether or not to politicize the ’India Against Corruption’ (IAC) movement. In India, political corruption and instability can be seen throughout the government system. Arvind Kejriwal took the controversial decision to fight the corrupt government system by directly joining politics. Exhibiting a bold and democratic attitude, Aam Aadmi Party demanded that India, as a democratic country, should become a nation with transparency, accountability, fair legislative system and common participation in government affairs. In the 2013 Delhi Assembly election, Aam Aadmi Party became the second largest vote-getter in the Delhi Assembly by winning 28 out of 70 seats. An important part of its agenda was to pass the Jan Lokpal Bill and make it a law in India. Due to the uncooperative attitude of other major political parties in India, Aam Aadmi Party resigned after being in government for just 49 days. In 2015, Aam Aadmi Party again won a historic victory by securing 67 out of 70 seats in Delhi Assembly with the resolve to clean up politics.